Population Structure of Echinoderms Associated with Seagrass on the South Coast of East Lombok - Fadilah, Nurjariati; Al Idrus, Agil; Syukur, Abdul (Jurnal Biologi Tropis, 2024)
The Population structure is the individuals within a population that can be grouped based on specific characteristics, such as age groups or age stratification, such as prereproductive, reproductive, and postreproductive stages. This study aims to assess the population structure of Echinoderms on the southern coast of East Lombok based on average size and determine association types. Data collection was conducted using the quadrant transect method. Subsequently, data analysis included average size values of Echinoderms, Association Index, and abundance (Di). The study identified eight species totaling 726 individuals across seven families. Among them, the species with the highest number of individuals in the Poton Bako area was Protoreaster nododus (27.82% of total individuals). Meanwhile, the species with the lowest number of individuals on Pantai Lungkak was Ophiocoma scolopendrina (0.55% of total individuals). The highest abundance value (Di) was found for Protoreaster nodosus at Poton Bako (0.20 ind/m2), while the lowest (Di) was found for Ophiocoma scolopendrina at Pantai Lungkak (0.00 ind/m2). The species with the longest average size was Synapta maculata (24.50±6.21 cm), included in reproductive stratification, and the smallest average size was for Ophiocoma scolopenderina (1.33±0.12 cm), included in reproductive stratification. There was an association of Echinoderms with seagrass beds, with a positive association observed in the Poton Bako area and a negative association observed in Pantai Lungkak.